Interaction between financial institution development and financial market development in MENA region: Its effect on economic growth - Hanoun, Raed; Taher, Hanadi (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of financial development on economic growth in twelve Middle East and North Africa (MENA) countries—Saudi Arabia, United Arab Emirates, Qatar, Oman, Kuwait, Bahrain, Lebanon, Turkey, Tunisia, Egypt, Jordan, and Morocco—over the period from 1990 to 2023. The interaction between financial institution development and financial market development is used as a proxy for overall financial development. Employing panel data techniques, including pooled ordinary least squares, fixed effects, and Driscoll–Kraay robust fixed effects models, the analysis highlights the positive role of the joint development of financial markets and institutions. Results reveal that the interaction between financial institution development and financial market development contributes to a 1.39 percentage point increase in economic growth. This finding underscores the synergistic effect of simultaneous advancement in both financial sectors in promoting growth across MENA economies. The study introduces an innovative measure of financial development by incorporating an interaction term between institutional and market development, offering new insights into the finance–growth nexus in the region.